Navigating Market Volatility: ESG and Islamic Stock Performance amidst Covid-19 Stringency - Agustin, Isnaini Nuzula; Safitri, Destiana; Hesniati, Hesniati; Robin, Robin (ETIKONOMI, 2025)
Research Originality:  This study examines the relationship between ESG and Islamic stocks under the exceptional circumstances of the COVID-19 pandemic. Researchers included the stock volatility and involved policy stringency, extending the recent literature focusing on accounting-based performance.Research Objectives: This study examines the relationship between ESG practices and Islamic stock performance during the COVID-19 pandemic.Research Methods: This study applied panel regression analysis. Researchers used Shariah-compliant stocks with ESG scores ranging from 2020 to 2022, resulting in 96 observations.Empirical Results: This study posits the ability of Social and Governance practices to reduce market volatility. The stringency of COVID-19 significantly affected stock volatility, highlighting the importance of government intervention during the Pandemic.Implications: These findings support the need for implementing measures and regulations that incentivize companies to adopt comprehensive ESG practices, which are expected to contribute to stock market stability, particularly during turbulent times.JEL Classification: J6, M2, O3How to Cite:Agustin, I. N., Safitri, D., Hesniati., & Robin. (2025). Navigating Market Volatility: ESG and Islamic Stock Performance Amidst Covid-19 Stringency. Etikonomi, 24(1), 69 – 84. https://doi.org/10.15408/etk.v24i1.38475.